Gravidez e Soropositividade para o HIV: vivências de mulheres atendidas em um centro de referência em HIV/AIDS - Camila Augusta dos Santos (2007)
It is about an ethnographic study whose objective was to understand the dealing with the pregnancy associated to the HIV infection by pregnant women that receive medical attention in public service centers. Developed together the 13 informers, with ages between 19 and 45 years old that have been treated in the Orestes Diniz Infectious and Parasite Diseases Training and Reference Center Centro de Treinamento e Referência em Doenças Infecciosas e Parasitárias (CTR/DIP) Orestes Diniz in Belo Horizonte municipality, Minas Gerais state, from March to June, 2007. The research was carried out by the qualitative approach because it incorporates the whole dimension and facilitates the deepening in the theme. The data collection consisted of the participant observation association as it is recommended by Leininger and ethnographic interview according to Spradley. The number of interviews had been defined by the data saturation criteria. The obtained data analysis was based at Leiningers proposition to the ethnographic interview. From the data analysis 7 (seven) cultural descriptors emerged that allowed the sub themes identification: The absence of an explanation about the anti-HIV test during pregnancy implicates in fear and despair, Becoming oneself a seropositive pregnant woman to the HIV changes it all, Non breast-feeding means the loss of the maternal identity. These sub themes constituted the support to the central theme: The impossibility of breast-feeding is the worst of all. The exhaustive reading and consideration on the interviews, the sub themes and the central theme were essential to extend the knowledge about beliefs, values, feelings and needs of the seropositive to the HIV pregnant woman who took part in this study. The discovery of the HIV infection during pregnancy intensifies the fears about the virus vertical transmission what reinforces on the future mothers the guiltiness feelings about the contamination. Living the impossibility of breast-feeding has been described by the informers as an experience marked by the loss feeling of a fundamental stage to whole motherhood perform. Non breast-feeding their babies was reported by the informers as an accusation about their unlikeness to the other ordinary mothers. This referring to the antenatal accompanied and HIV infection control in a specialized center was found as a positive experience to most of them.